Age Related Histological and Histochemical Studies on the Colon and Cloaca of Broiler Chickens - Rajpoot, Neeraj Singh (Indian Journal of Veterinary Anatomy, 2020)
The present study conducted on colon and cloaca of broiler chickens of different age showed that the organs possessed villi of varying shapes and size lined by simple columnar epithelium having columnar, goblet and endocrine cells. The propria was having a loose and irregular connective tissue along with lymphoid tissue and intestinal glands. The more numerous goblet cells and the glands showed presence of glycogen, mucins, weakly sulfated mucopolysaccharides, sialomucins, hyaluronic acid and acidic mucopolysaccharides by special stains. The number of goblet and endocrine cells, and the lymphoid tissue increased with the advancement of the age of the birds.